Understanding what affects psychological morbidity in informal carers when providing care at home for patients at the end of life: a systematic qualitative evidence synthesis - Kerin Bayliss; Tracey Shield; Alison Wearden; Jackie Flynn; Christine Rowland; Penny Bee; Morag Farquhar; Danielle Harris; Alexander Hodkinson; Maria Panagioti; Margaret Booth; David Cotterill; et al. (Health and Social Care Delivery Research)
Background Informal carers are central in supporting patients at the end of life, but this has substantial negative impacts on carers’ own mental health. When carers are unable to cope, this may affect their ability to support the patient and increase the likelihood of patient hospital admissions. Further, demographic changes mean demands for care at and before end of life are increasing and existing services will struggle to meet these demands. It is important to recognise carers as a vital resource and prevent adverse health outcomes from caregiving (and thereby limit their consequences). Large individual variation in the level of psychological morbidity from end-of-life caregiving suggests there is scope for interventions to improve carer mental health if we can understand the underlying factors. Objectives This meta-synthesis of qualitative studies aims to identify factors reported by carers as important to their mental health. Data sources Searches of MEDLINE, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, Social Science Citation Index, EMBASE, Cochrane Central Register of Controlled Trials, Database of Abstracts of Reviews of Effects, and Cochrane Qualitative Reviews 1 January 2009 to 24 November 2019 for empirical publications from Organization for Economic Cooperation and Development countries in English/Scandinavian on factors affecting adult carer mental health during end-of-life caregiving in home settings. Review methods Systematic qualitative meta-synthesis in collaboration with a Public Patient Involvement carer Review Advisory Panel, included thematic synthesis, followed by a best-fit framework synthesis, informed by principles of meta-ethnography. Critical Appraisal Skills Programme Qualitative Studies Checklist was used. Results Thirty-three eligible studies identified six themes encompassing factors perceived by carers to affect their mental health during end-of-life caregiving. These were: (1) the patient condition (including patient decline); (2) impact of caring responsibilities (including exhaustion, lack of time for own needs, isolation); (3) relationships (including quality of the patient–carer relationship); (4) finances (including financial concerns, impact on work); (5) carers’ internal processes (including loss of autonomy, lack of confidence, coping strategies); and (6) support (including lack of informal support, inadequacies in formal support information and care provision, limited collaboration, disjointed care). Reported strategies to improve mental health were linked to the final two themes, with suggestions on how to manage carers’ internal processes and build appropriate support. Findings correspond with literature 1998–2008, indicating consistency in factors affecting carers and adding validity to findings. Limitations The review was limited to caregiving in the home setting and studies from Organization for Economic Cooperation and Development countries published in English and Scandinavian. Identified papers predominantly considered carers of people with cancer, with little research into ethnic-minority perspectives. The review may therefore not fully encompass factors affecting carers of people with longer-term conditions, or those within other care settings, countries and population groups. Conclusions and future work A wide range of both internal and contextual factors may lead to psychological morbidity when caring for someone at the end of life. Future work within practice therefore requires a broad-based rather than narrow approach to sustaining and improving carer mental health. Future work within research requires collaboration between researchers and stakeholders within policy, commissioning, practice and carer organisations to develop solutions and assess their effectiveness. Further, researchers need to develop better models for factors affecting carer mental health and their interaction, to build a stronger evidence base and better guide interventions. Study registration This study is registered as PROSPERO CRD42019130279. Funding This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme as award number HSDR 18/01/01 and will be published in full in Health and Social Care Delivery Research. See the NIHR Journals Library website for further project information. Plain language summary Introduction Being a carer for a family member or friend at the end of their life can have an impact on the carer’s mental health. This includes depression, anxiety, stress and feeling overwhelmed. If carers feel unable to cope, they may be less able to look after their relative or friend. The mental health of carers must be a priority to help them feel better, cope, and support patients. This review summarises information from research into things that carers say are important for their mental health, to help us understand how we may be able to maintain or improve carers’ mental health. Methods We worked with six carers in a Review Advisory Panel to search for studies on carers’ experience published between 1 January 2009 and 24 November 2019 and identify common themes from identified studies. Themes were put into a table of themes and subthemes, assessed by the carers, and compared with other literature to identify factors that caused carers to have poor mental health, and ways to help carers feel better. Results We found six themes that indicate how caring for those at the end of life can affect mental health. These include: the impact of the patient condition and seeing the patient decline; the impact of caring responsibilities; carers’ relationship with the patient; finances; carers’ feelings and experiences such as lack of control or confidence when caring; and support from other family, friends and health-care professionals. Strategies to improve mental health were linked to the final two themes, including how to manage carers’ views and experiences of their situation and how to gain appropriate support. Conclusions This study describes factors that lead to poor mental health and ways to improve mental health when caring for someone at the end of life. Further work is needed to use this information to inform policy and service delivery.